The tensile properties of chitosan filled polypropylene (PP) composites treated with acetic acid - Faisal, Amri; Salmah, Husseinsyah, Dr. Ir.; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.